Prognostic Impact of Hyponatremia and Hypernatremia in COVID-19 Pneumonia. A HOPE-COVID-19 (Health Outcome Predictive Evaluation for COVID-19) Registry Analysis - Ruiz-Sánchez, Jorge Gabriel; Núñez-Gil, Ivan J.; Cuesta, Martin; Rubio, Miguel A.; Maroun-Eid, Charbel; Arroyo-Espliguero, Ramón; Romero, Rodolfo; Becerra-Muñoz, Victor Manuel; Uribarri, Aitor; Feltes, Gisela; Trabattoni, Daniela; Molina, María; et al. (Frontiers in Endocrinology, 2020)
Dysnatremia are associated with increased mortality in patients with community-acquired pneumonia. SARS-COV2 (Severe-acute-respiratory syndrome caused by Coronavirus-type 2) pneumonia can be fatal. The aim of this study was to ascertain whether admittance dysnatremia is associated with mortality, sepsis, and need for mechanical ventilation (MV) of patients hospitalized with SARS-COV2 pneumonia. This is a retrospective study of the HOPE-COVID-19 registry, with data collected from January-1th through April-31th, 2020. We selected all hospitalized adult patients with confirmed SARS-COV2 pneumonia and a registered admission serum sodium (SNa). Patients were classified as hyponatremic (SNa <135 mmol/L), eunatremic (SNa 135-145 mmol/L), or hypernatremic (SNa >145 mmol/L). Multivariable analyses were performed to elucidate independent relationships of admission hyponatremia and hypernatremia, with mortality, sepsis and MV during hospitalization. 4664 patients were analyzed, median age 52 years [66-77], 58% males. Death occurred in 988 (21.2%) patients, sepsis was diagnosed in 551 (12%) and MV was required in 838 (18.4%). Hyponatremia was present in 957/4664 (25%) patients, and Hypernatremia in 174/4664 (3.7%). Both Hyponatremia and hypernatremia were associated with mortality and sepsis. Only hyponatremia was associated with MV. In conclusion, Hyponatremia and hypernatremia at admission are factors independently associated with mortality and sepsis in patients hospitalized with SARS-COV2 pneumonia.